Developing Writing Intensive Course Module: A Needs Analysis - Fortinasari, Paulina Besty; Malasari, Susanti (FKIP - Universitas Tanjungpura, 2025)
This research focuses on the needs analysis of developing a beginner-level learning module, which is in the initial stage. It applied a qualitative method in which data were gathered using a questionnaire and interviews. These data were descriptively analyzed using data condensation. The subjects of this research were 100 students and 4 lecturers. The results show that there is an urgent task because there is no course module for the Writing Intensive Course. It is also found that the existing material is suitable, but it needs to be added to the weekly theme to provide brainstorming space for the students. In terms of lack, want, and necessity, the learning modules must refer to the beginner level, accommodate the students to produce meaningful English sentences correctly, give more opportunities to exercise inside and outside the classroom, get more feedback from the lecturer, and integrate PjBL and case-method learning models. There were also some topics ranked based on students